PERANAN KOMUNIKASI PARIWISATA DINAS PARIWISATA KOTA MEDAN DALAM PENGEMBANGAN WISATA HERITAGE BAGI KAUM MILENIAL - Elok Perwirawati; Helen s Vanhurk Sriwati Ningsih Sitorus (Jurnal Ranah Komunikasi, 2020)
development of heritage tourism is closely related to cultural and historical issues as identity and identity of a nation. Millennials' sense of pride in history and culture has recently started to fade along with technological developments and the entry of foreign cultures to Indonesia. This research concludes that the Medan City Tourism Office has conducted tourism communications. First, communicating heritage tourist destinations through the brand “Colorful Medan”. Second, communicating accessibility to heritage tourist destinations through the “Medan Tourism” mobile app, leaflets, booklets and directions. Third, apply communication skills to human resources by forming a special team in conducting tourism marketing through social networks, the “Medan Tourism” mobile app and the official website of the Medan City Tourism Office. However, the results of the research show that what the Medan City Tourism Office is doing has not been maximized as the “Colorful Medan” brand is less well known by millennials, there is no special map related to heritage tourist destinations in one click menu on the mobile app “Medan Tourism”, the website incomplete and not up to date so that millennials do not get maximum tourist information.